Modelling trends in woody vegetation structure in semi-arid Australia as determined from aerial photography. - Fensham, Roderick John; Choy, Sama J. Low; Fairfax, Russell James (Journal of Environmental Management, 2003)
Accounting of carbon stocks in woody vegetation for greenhouse purposes requires definition of medium term trends with accurate error assessment. Tree and shrub cover was sampled through time at randomly located sites over a large area of central Queensland, Australia using aerial photography from 1945 to 1999. Calibration models developed from field data for the same land types as those represented within the study area allowed for the extrapolation of overstorey and understorey cover, basal area and biomass values and these were modelled as trends over the latter half of the 20th century. These structural attributes have declined over the region because of land clearing with values for biomass changing from a mean of 58.0(± 1.2)t/ha in 1953 to 41.1(± 1.0)t/ha in 1991. The biomass of Acacia on clay and Eucalypt on texture contrast soils land types has declined most dramatically. Within uncleared vegetation there was an overall trend of increase from 56.1(±1.2)t/ha in 1951 to 67.6(± 1.3)t/ha in 1995. The increase in structural attributes within uncleared vegetation was most pronounced for the Eucalypt on texture contrast soils and Eucalypt on clay land types. It was demonstrated that the sites sampled were representative of their land types and that spatial bias of the photography, undetected tree-killing, sampling error, inherent variability of structural attributes and measurement error should not have impacted greatly on bias or precision of trend estimates for well-sampled land types. Certainly the errors are not likely to be substantial for trends averaged over all land types and they provide an accurate assessment of the magnitude and direction of change. The technique presented here would appear to be a robust means of accounting for the above-ground woody component of woodlands and open forests and will also contribute to a broader understanding of savanna dynamics. Copyright (c) 2003 Elsevier Ltd